AB0599 TREATMENT OF REFRACTORY DERMATOMYOSITIS WITH TOFACITINIB. (2nd June 2020) - Riggle, K.; Patel, A.; Aggarwal, R.
Abstract : Background: Dermatomyositis (DM) is a systemic, autoimmune disease affecting the skin and proximal skeletal muscles. A subset of DM patients present with subclinical or resolved muscle involvement but continue to have skin disease. In these cases, first and second line treatments including glucocorticoids are sometimes insufficient for controlling the disease, necessitating escalation of treatment. Several recent studies have investigated the response of Tofacitinib, an oral Janus Kinase inhibitor approved for the treatment of rheumatoid arthritis, in DM patients and patients with inflammatory skin diseases. Objectives: Due to the reported ability of JAK inhibitors to suppress type 1 interferon (IFN) signaling, which is suspected to be upregulated in DM, we evaluated the efficacy of treatment with Tofacitinib in four refractory DM patients. Methods: Four patients with dermatomyositis without evidence of current muscle involvement began treatment with Tofacitinib 11 mg daily after they had failed or had adverse effects to first and second line immunosuppressive agents. Their medical records were reviewed at 0, 3, and 6 months, with improvement measured using the Cutaneous Dermatomyositis Disease Area and Severity Index (CDASI) activity score. Throughout their treatment they were additionally monitored for improvement in markers of inflammation and the necessity for concomitant treatments. Patients were monitored for adverse effects to Tofacitinib treatment. Results: All four patients within the case series showed significant improvement of their cutaneous disease activity (CDASI scores improved by 8-15 points) over the first 6 months, with three of the four having achieved minimal clinically improved difference of >= 5 point by three months. Based on the CDASI, three of the cases' disease classification changed from moderate-to-severe disease to mild disease. The last patient initially presented with mild disease. Other outcomes noted included improved pruritus in 3 patients and improvement of calcinosis in 1 patient. One patient was additionally able to stop concomitant treatment with prednisone and IVIG at 3 and 6 months, respectively. This patient had been on daily prednisone for 4 years. Only other patient on prednisone was on low dose of 3mg daily. The patients all had normal muscle exams prior to treatment with Tofacitinib. No worsening muscle involvement or adverse effects were noted with Tofacitinib use. Conclusion: Tofacitinib is believed to play a role in the inhibition of IFN signaling pathways that are overactive in dermatomyositis. All four patients within this retrospective study showed significant improvement of cutaneous disease with Tofacitinib use. References: [1]Moghadam-Kia S. Rheumatology . 2019;58(6):1011-1015. [2]Kurtzman D. JAMA Dermatol . 2016;152(8):944. [3]Paik J. Semin Arthritis Rheum . 2017;46(4):e19. [4]Kurasawa K. Rheumatology . 2018;57(12):2114-2119. [5]Anyanwu CO. Br J Dermatol . 2015; 173(4):969-974. Disclosure of Interests: Kirsten Riggle: None declared, Aarat Patel Speakers bureau: Abbvie, Mallinckrodt, Celgene, Lilly, Rohit Aggarwal Grant/research support from: Pfizer, Genentech, BMS, Mallinckrodt, Consultant of: Pfizer, Genentech, BMS, Mallinckrodt, Bristol Myers-Squibb, octapharma, CSL Behring, AstraZeneca, Corbus, Kezar, Abbvie